Оцінка відповідності структури природоохоронних територій європейських країн критеріям МСОП - Дядченко, Владислав Валерійович; Каракуркчі, Ганна Володимирівна; Петрухін, Сергій Юрійович; Дядченко, А. В.; Кочанов, Е. О.; Максименко, Н. В.; Шумілова, А. В. (Харківський національний університет ім. В. Н. Каразіна, 2016)
На основі отриманих даних зроблено розподіл та порівняння категорій природо-охороних територій Польщі, Німечини, України, Великої Британії і Франції з критеріями Міжнародної спілки охорони природи (МСОП). Визначено перспективні напрямки розширення площ ПЗФ названих країн, згідно вимогам МСОП.

Analyzed of environmental law of European countries (Poland, Germany, United Kingdom, France), his the history and present structure of protected areas. On the basis of the data carried out distribution and comparison of categories of protected areas in Poland, Germany, Ukraine, Great Britain and France with the IUCN criteria. Defined of perspective directions of expansion of protected areas of these countries, according to IUCN requirements. Ukraine has a very low percentage of protected areas among European countries and it should be gradually increased. According to the research, in Ukraine there is an urgent need to increase the area of protected areas in categories I and III IUCN, namely strict protection areas (reserves) and natural monuments. For France, it is necessary to create conservation areas that meet the IUCN category, and for the UK-III category of IUCN.
Assessment of conformity environmental territories of european countries to criteria of IUCN
Keywords: національні парки; заповідники; заказники; пам'ятки природи; регіональні ландшафтні парки; резерват; екологічне законодавство; national parks; wilderness area; national monument; species management area; regional landscape parks; protected area with sustainable use; protected landscape